Membrane distillation (MD) processes for water desalination applications. Can dense selfstanding membranes compete with microporous hydrophobic materials?. (12th October 2018) - Mejia Mendez, Deisy Lizeth; Castel, Christophe; Lemaitre, Cecile; Favre, Eric
Highlights: Dense membrane productivity compete with microporous membranes. Two fold potential increase in water flux with thin dense membranes. Thermal efficiency unaffected by dense membranes. Simulation provides good prediction of experimental results. Abstract: Membrane distillation (MD) is considered as a key technology for desalination applications. It shows indeed numerous advantages compared to reverse osmosis and other desalination processes (e.g. thermal driving force, no osmotic pressure effect on membrane fluxes). Nevertheless, this technology still presents some issues, most notably due to pore wetting effects. This study proposes the use of a thin, self-standing dense membrane in place of microporous materials as a solution to avoid wetting in MD for water desalination. In a first step, a membrane contactor model is developed based on mass and energy balances and the simulations are validated using experimental results obtained on hollow fiber modules with microporous membranes. A comparative performance analysis is then achieved between a porous and a dense membrane module. A parametric study on the influence of dense membrane thickness and water permeability shows that a two fold increase in water flux, without significant impact on energy efficiency, is potentially achievable with thin and permeable dense materials compared to microporous membranes. Guidelines for the design of high-performance dense membrane modules for MD are finally proposed.